Pengaruh Aspirasi Karir, Panggilan Karir, Dan Kesadaran Peluang Terhadap Persepsi Kelayakan Kerja - Ratri Nastiti, Prianka (Universitas Ngudi Waluyo, 2022)
Perceptions of employability, career aspirations, career calling factors, and awareness of opportunities are important factors that need to be taken into account for alumni and final year students in higher education because it involves the preparation and readiness they face after graduating from college, namely when they enter the world of work. actually. This study uses a sample of alumni and final year students of public and private universities in the city of Semarang. The sample used is 100 respondents and data processing is done using SMART PLS3. The results show that career aspiration does not have an effect on perceptions of employability, career calling does not have an effect on perceptions of employability, and awareness of opportunity has a positive and significant impact on perception of employability.